(untitled) (Archives of Pediatrics of Uruguay, 2025)
Myelomeningocele is the most common malformation of the central nervous system, associated with funcional by functional limitations and neuro-musculoskeletal, nephr-urological o nephro and intestinal complications with the consequent social and psychological repercussions on the individuals who present it. Fetal surgery with repair of the defect is, worldwide and in Uruguay, currently, the first line treatment option today. In Uruguay, almost 20 fetal surgeries have been performed with the SAFER technique. The objective of this atlas is to guide clinicians in the appropriate neonatal evaluation and treatment of patients who underwent surgery in the fetal period. A postnatal multidisciplinary approach guide for the newborn is presented with illustrative images, and recommendations on neonatological and long-term neurosurgical, neuropediatric, and urological follow-up, among others. We highlight the importance of the comprehensive, individualized and multidisciplinary assessment that these patients require to optimize surgical and functional results.